Nonlinear State Estimation and Control of Autonomous Aerial Robots: Design and Experimental Validation of Smartphone Based Quadrotor - Hayajneh, Mohammad Radi Mohammad <1987> (Alma Mater Studiorum - Università di Bologna, 2016)
This work presents developments of Guidance, Navigation and Control (GNC) systems with application to autonomous Unmanned Aerial Vehicle (UAV). Precisely, this work shows the development of navigation system based on nonlinear complementary filters for position, velocity and attitude estimation using low-cost sensors. The proposed filtering method provides attitude estimates in quaternion representations and position and velocity estimates by fusing measurements from Inertial Measurement Unit (IMU), GPS, and a barometer. Least Square Method (LSM) was used in gains tuning to find the best-fitting of the estimated states with precise measurements obtained by a vision based motion capture system. A complete navigation system was produced by integrating both the attitude and the position filters. The integration of the filtering approach based primarily on the ease of design and computational load. Furthermore, the structure of the filtering design allow for straightforward implementation without a need of high performance signal processing. Moreover, the filters can be tuned totally independent of each other. This work also introduces a nonlinear flight controller for stability and trajectory tracking that is practical for real-time implementation. This controller is also demonstrated the ability of a supervisory controller to provide effective waypoint navigation capabilities in autonomous UAV. The implementation of the guidance, navigation, and control algorithms were adopted in the design of a novel smartphone based autopilot for particular quadrotor aerial platforms. The performances of the proposed work are then evaluated by means of several flight tests. The work also includes a design of advanced navigation and guidance systems based on Robot Operating System (ROS) for Search And Rescue (SAR) missions. Primarily, the performance of the navigation and guidance systems were tested in laboratory by simulating GPS measurements in Linux computer mounted on the top of a quadrotor. This activity facilitates moving by the experiments from indoor to outdoor.